Tuberculous Lymphadenitis Mimicking Nodal Metastasis in Follicular Variant Papillary Thyroid Carcinoma - Marc Gregory Yu; Jenny Maureen Atun (Case Reports in Medicine)
Tuberculous (TB) lymphadenitis can mimic cervical node metastasis from papillary thyroid carcinoma (PTC) since the distribution and appearance of affected lymph nodes are similar. We present the case of an asymptomatic 50-year-old Filipino who sought consult for a gradually enlarging anterior neck mass and a single palpable cervical lymph node. Preoperative workup suggested a thyroid malignancy with nodal metastasis. He underwent total thyroidectomy with node dissection where histopathology confirmed follicular variant- (FV-) PTC. Lymph node examination, however, revealed TB lymphadenitis, and the patient was given standard antimycobacterial therapy. This is the first documented case in Southeast Asia, a high TB burden region. This is also the first report involving FV-PTC, which has features between those of conventional PTC and follicular thyroid carcinoma. The case suggests that, in endemic areas, TB should be a differential in the etiology of cervical lymphadenopathy in PTC patients. In developed countries, this differential diagnosis is also valuable because of the increasing incidence of HIV and TB coinfection. Proper preoperative evaluation is important and needs to be highlighted in the formulation of local guidelines.